Perhitungan Biaya Perkuatan Struktur Bangunan Hotel Eksisting Berdasarkan SNI 1726:2012 Menggunakan Carbon Fiber Reinforced Polymer (CFRP) - Aviska Triayaska; Hanie Teki Tjendani; Buntara Sthenly Gan (Jurnal Spesialis Teknik Sipil (JSpTS), 2026)
The change in earthquake standards from SNI 1726:2012 to SNI 1726:2019 has increased earthquake load demands in several regions in Indonesia, including Surabaya City, so an evaluation of the safety of existing buildings is needed. This study aims to calculate the cost of strengthening the structure of an existing hotel building using the Carbon Fiber Reinforced Polymer (CFRP) method due to increased earthquake loads based on the latest standards. The object of the study is a 10-story hotel building designed using SNI 1726:2012. Structural analysis was carried out using SAP2000 V.26.3.0 with the pushover analysis method based on ASCE 41-17 to determine structural elements that require rehabilitation. Elements that experience performance exceeding the Collapse Prevention (CP) limit are planned to use CFRP reinforcement according to ACI 440.2R-17 guidelines. Furthermore, the calculation of the work volume and the Cost Budget Plan (RAB) was carried out based on the unit price of work in Surabaya City. The results of the study indicate that the B6-1 Beam element (150 mm × 400 mm) on several floors requires CFRP reinforcement with a total work volume of 28.35 m2. Based on the results of the cost analysis, the unit price of the work is Rp. 2,389,987.46/m2 with a total rehabilitation cost of Rp. 67,756,144.46. The use of CFRP is considered effective in increasing the capacity and ductility of the structure without significantly increasing the building mass, although it has a relatively high initial cost compared to conventional methods.